Sacajawea : the story of Bird Woman and the Lewis and Clark Expedition - Bruchac, Joseph, 1942- (San Diego, CA : Silver Whistle, 2001)
Sacajawea, a Shoshoni Indian interpreter, peacemaker, and guide, and William Clark alternate in describing their experiences on the Lewis and Clark Expedition to the Northwest.
Includes bibliographical references (p. [200]).
G6
Keywords: Sacagawea -- Juvenile fiction; Clark, William, -- 1770-1838 -- Juvenile fiction; Sacagawea -- Fiction; Clark, William, -- 1770-1838 -- Fiction; Shoshoni Indians -- Fiction; Indians of North America -- Fiction